EFFECTS OF COPPER MICROPARTICLES ON THE GROWTH AND SURVIVAL OF JUVENILE RAINBOW TROUT (ONCORHYNCHUS MYKISS WAL.) - Savic, Nebojsa (Journal of Agricultural Sciences (Belgrade), 2021)
During the farmed of juvenile rainbow trout (Oncorhynchus mykiss), losses can be very high. In aquaculture, various agents are used, such as copper, for the purpose of preventive action and prevention of the appearance of pathogens (ectoparasites, etc.). The aim of this study was to determine the effects of substrate-fixed copper microparticles on the growth and survival of juvenile rainbow trout (Oncorhynchus mykiss) from swimming to 5 months of age. The experiment was realized in the Laboratory for Aquaculture of the Faculty of Agriculture, University of Banja Luka, for 142 days in flow aquariums with a volume of 65 l / aquarium. The experiment was set up in two groups (150 units / group) with three replicates (50 units / replicate), a control group without copper microparticles (K) and a group with copper microparticles (Cu). The initial weight and total body length (mean±SD) of rainbow trout in group K were 0.199±0.008 g and 2.876±0.036 cm, and in group Cu 0.197±0.009 g and 2.893±0.038 cm. The average total length and body weight of individuals from the K and Cu groups were similar (p > 0.05). The differences FCR, CF, SGR and TGC between group K and group Cu were not statistically significant (p > 0.05). Survival of juvenile rainbow trout was high and was 97.33% in group K and 96.00% in group Cu, no statistically significant difference was found (p> 0.05). The growth and survival of juvenile rainbow trout in the K and Cu groups is similar.
Keywords: microparticles, copper, growth, survival, juvenile, rainbow trout